Geographic diversity of the Streptococcus equi subsp. equi accessory genome: implications for vaccines and global surveillance - He, Lingyu; Khine, Nwai Oo; Song, Jeongmin; Loubière, Celine; Butaye, Patrick (Frontiers in Veterinary Science, 2025)
Strangles, caused by the host-adapted Streptococcus equi subsp. equi (S. equi), imposes significant welfare and economic losses on the equine industry worldwide. Understanding its genomic features, virulence-associated genes (VAGs), antimicrobial resistance (AMR) and mobile genetic elements (MGEs) is essential for disease control and vaccine development. This study aimed to characterize the accessory genome composition, geographic distribution of VAGs and MGEs, and AMR profiles of S. equi by a large-scale genomic analysis of global publicly available S. equi sequences. All publicly available S. equi sequences in the Sequence Read Archive (SRA) database were retrieved and assembled. A total of 552 high-quality assemblies were obtained for further analysis. The strains originated from five continents (North/South America, Europe, Asia and Oceania). The geographical distribution of VAGs (analyzed using an in-house Streptococcus equi virulence factor database), antibiotic resistance gene (ARG) profiles, and the contribution of MGEs to S. equi VAGs were analyzed in this study. The results revealed that S. equi exhibited a closed pangenome with 1,661 core and 982 accessory genes. Among 71 identified VAGs, 40 were core VAGs, while accessory VAGs showed significant geographic variations, especially in nutritional/metabolic factor genes and exotoxin genes. No acquired ARGs were detected except a single qacG gene encoding resistance to quaternary ammonium compounds. This study revealed a functional specialization of MGEs, where prophages carry superantigen genes (speH, speI) and the hyaluronidase gene hylP; genomic islands (GIs) harbor iron acquisition genes (eqb cluster) and the virD4 gene encoding the T4SS coupling protein; and integrative conjugative elements (ICEs) carry the heme metabolism cluster (htsA, shp) and streptolysin S-associated genes (sagA, sagD). The geographic variation of VAGs suggests regional adaptive pressures and supports genome streamlining in S. equi. In conclusion, S. equi exhibits a closed and streamlined genome, characteristic of host-adapted bacteria. There is a minimal acquisition of ARGs while key VAGs are retained. Prophages, GIs, and ICEs play specialized roles in VAG distribution. These findings provide insights into prioritizing VAGs for strangles vaccine development and surveillance of antigenic variation to mitigate vaccine escape.